Secular Partisan Realignment in the United States: The Socioeconomic Reconfiguration of White Partisan Support since the New Deal Era. (September 2019) - Kitschelt, Herbert P.; Rehm, Philipp
White American voters have realigned among the two dominant parties by income and education levels. This article argues that the interaction of education and income provides a more insightful—and stark—display of this change than treating them individually. Each group of voters is associated with distinctive "first dimension" views of economic redistribution and "second dimension" preferences concerning salient sociopolitical issues of civic and cultural liberties, race, and immigration. Macro-level hypotheses are developed about the changing voting behavior of education-income voting groups along with micro-level hypotheses about the propensity of vote switching. The hypotheses are tested with data from the American National Election Studies 1952–2016. A profound realignment is revealed between (groups of) white voters and the two main US parties that is consistent with the theoretical expectations developed in the article.